Tele-control in bulk water system - Huraini Z.M.I. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The target of using Tele-Control in Bulk Water System is to facilitate and improve maintenance and operation of the water projects in Palestine by applying of the tele-control system in water supply networks, storage and pressure regulating reservoirs, wells and booster stations. Which will give us a better control of water losses, black losses, water leakage and the pressure zones where the consumer's services, quality of water and availability and reliability of supplying water will be improved for the Palestinian inhabitants. The SCADA System involves the full upgrading of the water supply and distribution system in Palestine, rehabilitation of the main water sources, replacement of the water distribution networks, constructing and refurbishment of the storage reservoirs and collecting the required information's data.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)